Strategi Pemasaran Produk Usaha Ternak Ayam Petelur di Desa Senganan Kecamatan Penebel Kabupaten Tabanan - I WAYAN ALDI MAHENDRA; I WAYAN BUDIASA; WIDHIANTHINI WIDHIANTHINI (Jurnal Agribisnis dan Agrowisata (Journal of Agribusiness and Agritourism), 2022)
The Product Marketing Strategy for Laying Chicken Livestock in Senganan Village, Penebel District, Tabanan Regency The laying chicken breeders in Senganan Village face problems that are still not resolved, including marketing has not met the desired target, farmers have not maximized existing technology, and business capital is still limited, and lack of manpower. The purpose of this research was to determine the internal and external factors faced by laying hens in marketing their products and to formulate strategies to promote their production. The data collection technique used in this research is the survey method with the method of determining the sample with saturated sampling. The data analysis method used in this research is the Strengths, Weaknesses, Opportunities and Threats (SWOT) analysis method and the Quantitative Strategic Planning Matrix (QSPM) analysis method. The results showed that (1) Internal factors were divided into two, namely strength factors, namely egg quality and customer relations, while the main weakness was that marketing had not met the target. External factors are divided into two, namely the opportunity factor which describes that the demand for eggs is very high but all of it can’t be fulfilled, while the main threat is price fluctuations, especially the price of feed and vaccine. (2) The marketing strategy for laying hens for a small scale is to good plan marketing and build good relationships with buyers. For medium scale by planning the chicken coop layout in accordance with regulations but still optimizing maintenance of the cage to get good eggs quality and determine sales strategy. For large scale, by offering an attractive work and salary system for prospective workers, including the provision of performance bonuses when using workers.